Stocking rate and supplementation of steers grazing bluestem pasture in early summer - Smith, E.F.; Riley, Jack G.; Owensby, Clenton E.; Schalles, R.R.; Graber, Ronald W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Native bluestem pastures were grazed from May 8 to July 18, 1984 by steers with an average beginning weight of 553 lb, at stocking rates of 1.7, 1.5, and 1.25 acres per steer. Gains per acre were higher (P<.01) with increased stocking rate (97, 111, 132 lb/acre). Daily gains were similar for the three stocking rates (2.34, 2.35, 2.36 lb/day). Daily supplementation with about 1.5 lb sorghum grain plus Rumensin® per head significantly increased gains.
Keywords: Beef; Stocking rate; Steers; Bluestem